دور الوقف التنموي في الحضارة الإسلامية (The Developmental Role of Endowment in the Islamic Civilization) - أحمد علوي السقاف , (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
أبرز النبي صلى الله عليه وسلم ملامح الدولة الإسلامية ومقاصدها، وتجلى ذلك في أول القرارات الصادرة منه وهو إنشاء مقر تنطلق منه فعاليات هذه الدولة الفتية وهو المسجد، وتأسيس علاقة اجتماعية تضامنية تجانس المجتمع الجديد وهي المؤاخاة بين المهاجرين والأنصار ووثيقة تبين العلاقة بين مكونات مجتمع المدينة وهي وثيقة المدينة. تسعى هذ الدراسة إلى بيان إسهامات الوقف في التنمية العلمية، وتطور محاضن التعليم، ونشأة المدراس الإسلامية، ودور الوقف في الرعاية الصحية وبناء المستشفيات. من نتائج الدراسة ما يأتي: اتضح مما سبق الدور الكبير الذي قام به نظام الوقف في ازدهار الحضارة الإسلامية على وجه العموم وفي نظام التعليم والصحة على وجه الخصوص، وتبين لنا دور الوقف وتأثيره في توجيه الفكر، وكيف أدت المدارس الوقفية والتي قيدها الواقفون بشروط منهجية في نشر المنهج أو المذهب الذي حدده الواقف، وفي الجانب الصحي عملت الأوقاف الصحية نقلة نوعية في الرعاية الصحية وانعكس ذلك على حياة الناس، وإن الخدمات التعليمية والصحية عندما تخرج من الإطار النفعي والربحي، قد يكون لها أثر سلبي؛ حيث يتعامل معها سلعة. الكلمات المفتاحية: الوقف، التعليم، المدارس الدينية، الرعاية الصحية. Abstract The Prophet (PBUH) had highlighted the features of the Islamic state and its purposes. This was manifested amongst the very first decisions he (PBUH) made, one of them was the establishment of mosque, where the activities of this young state started, as well as the establishment of a social and solidarity relationship between the al-muhajirun and the ansar. Among the decisions also was the declaration of the Constitution of Medina, the constitution that declared relationship between the entities of Medina settlers. This study seeks to demonstrate the contributions of the Waqf to scientific development, the development of educational incubators, the emergence of Islamic schools, the role of the Waqf in health care and the construction of hospitals. The results of the study indicate that Waqf system played a significant role in flourishing Islamic civilization in general and in the education system and health in particular. It also shows us the role of the Waqf in guiding thoughts and spreading curriculum or doctrine defined by the endowers. On the health side, the Waqf has led to a paradigm shift, and hence reflected on the lives of people. The study also indicates that excluding educational and health services out of the beneficial and profitable framework, it may have negative effects. Keywords: Endowment, Education, Islamic School, Healthcare.